An algorithm for infectious screening of corneal donors in eye tissue bank of the Fyodorov Eye Microsurgery Federal State Institution - S.A. Borzenok; M.Yu. Gerasimov; Yu.A. Komakh; M.Kh. Khubetsova; H.D. Tonaeva; L.M. Malikova; P.I. Plaksa (Офтальмохирургия)
Purpose. To analyze an algorithm for infectious screening of cadaver corneal donors during corneal processing at the Eye Tissue Bank (ETB) of The Fyodorov Eye Microsurgery Federal State Institution and compare it with the European Eye Bank Association (EEBA) data from 2011 through 2015. Material and methods. Data analysis were done using the ETB in-house donor data registry and EEBA annual directory forms. The extracted data included the number of received eye globes, rates of inconclusive and serological tests for human immunodeficiency virus (type 1 and 2), Hepatitis B and C viruses, and Syphilis. Results. During the analyzed period 3479 eye globes were delivered in the ETB for the processing. Hemolysis caused exclusion for 13.9% (n=486) of corneas in the ETB. In opposite, the EEBA data demonstrated far lower rates of inconclusive tests. The positive serology tests lead to canceling 19.4% (n=676) of the incoming corneas in the ETB. Overall, the rates of positive tests were far higher in comparison with EEBA data. At the ETB, positive serological tests for HIV (type 1 and 2) and Syphilis had low variability annually, while the rates of Hepatitis B increased in 2015. Predomination of Hepatitis C was also noted. Often enough, the blood samples were multiply-infected. Conclusion. Overall, the positive serology and hemolysis were the major contraindications and led to exclusion 33.4% (n=1162) of incoming corneas in the ETB. Serological tests rates for indicated infections were higher in the ETB with predomination of Hepatitis C. An algorithm for infectious screening at the Eye Tissue Bank (ETB) of The S. Fyodorov Eye Microsurgery Federal State Institution was effective in selection of postmortem donors for cornea processing in clinical use.